ANALISIS KELAYAKAN INDUSTRI PENGOLAHAN TEH HERBAL (Euphorbia hirta) DENGAN KOMBINASI TEH HITAM (Camellia sinensis) - Agung Nugroho; Hesty Heryani; Wiwin Tyas Istikowati (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Degenerative diseases have been reported as the main causes of mortality number in Indonesia. An unhealthy lifestyle, including lack of exercise combined with low of fiber and antioxidants diet, is believed as the main triggering factor. Functional foods which offer several benefits, including its built-in nutrition, the pharmacological effects, as well as the practical uses, is considered as one of the effective solutions to supply the antioxidant deficiency. Euphorbia hirta is an herbaceous plant that has been reported to have several important pharmacological activities, including in the prevention of some degenerative diseases through its antioxidative capacity. A type of functional food enriched with antioxidant has been formulated from the leaves of E. hirta and black tea (Camellia sinensis); however, the feasibility analysis of its processing industry has not been carried out. This study was aimed to analyze the marketing, technical, management, and financial feasibility of establishment of functional food industry of E. hirta herb combined with black tea. The feasibility was analyzed by considering the marketing aspects, technical aspects (process technology and plant layout), management aspects, and financial aspects as measured by the NPV, Net B/C, IRR, PBP, and BEP values. The financial analysis showed that the NPV was Rp81,520,549.00 with 1.30 of Net B/C, 27.64% of IRR, and 2.6 years of PBP. Based on the results, the planned industry is declared to be feasible especially in the aspects of marketing, technic, management, and financial.